Mechanism and Effect of Mallet Tapping on Contact Stress Distribution Between V-band Clamp and Piping Systems - Zhang, Zhengui; Zhang, Haiyan H.; Wu, Peixuan (International Journal of Industrial Engineering and Management, 2014)
This paper is dedicated to investigate the mechanism of mallet tapping on the equalization of contact pressure distribution between V-band clamp and piping system. A sensor platform with charge mode amplifier is built to collect quasi-static measurements of contact pressure during loading. Contact pressures in the initial stage before and after mallet tapping is measured using piezoelectric sensor tests. Finite element analysis (FEA) is carried out to find the initial contact areas. The controlled measurement verified the viability of mallet tapping on contact pressure redistribution. In terms of clamping stability, the effect of mallet tapping is discussed from the working principle of Vibratory Stress Relief (VSR). Dynamic analysis is also tried to explore the mechanism of mallet tapping on equalizing the contact pressure distribution. The frequencies of clamp are estimated by theoretical calculation and experiment tests, which are applied to derive the mode of vibration wave after mallet tapping. Article history: Received (02.02.2014.); Revised (27.05.2014.); Accepted (30.06.2014.)